The Influence of Discipline and Motivation on Employee Job Satisfaction Levels in Non-Bank Financial Institutions in West Java - Tarisha Ridha Yasmin; Andhika Mochamad Siddiq; Arie Hendra Saputro (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
Employeee job satisfaction is a key factor in supporting company performance and long-term success, especially in West Java's non-bank financial institutions. These institutions face problems with employeee lateness, which shows low job satisfaction. This issue is likely caused by poor work discipline and low employeee motivation. This study aims to analyze the effect of work discipline and motivation on employeee job satisfaction. The method used is quantitative with descriptive and verificative approaches. There were 45 respondents, which is the total number of employeees at the West Java non-bank financial institution. The data was analyzed using multiple linear regression with statistical software. Results show that work discipline and motivation have a positive and significant effect on employeee job satisfaction, both separately and together. Work motivation has a stronger effect than work discipline. The study concludes that better job satisfaction can be achieved through consistent work discipline and ongoing motivation improvements.